Low background and high contrast PET imaging of amyloid-β with [(11)C]AZD2995 and [(11)C]AZD2184 in Alzheimer’s disease patients - Forsberg, Anton (Springer-Verlag, 2013)
PURPOSE: The aim of this study was to evaluate AZD2995 side by side with AZD2184 as novel PET radioligands for imaging of amyloid-β in Alzheimer’s disease (AD). METHODS: In vitro binding of tritium-labelled AZD2995 and AZD2184 was studied and compared with that of the established amyloid-β PET radioligand PIB. Subsequently, a first-in-human in vivo PET study was performed using [(11)C]AZD2995 and [(11)C]AZD2184 in three healthy control subjects and seven AD patients. RESULTS: AZD2995, AZD2184 and PIB were found to share the same binding site to amyloid-β. [(3)H]AZD2995 had the highest signal-to-background ratio in brain tissue from patients with AD as well as in transgenic mice. However, [(11)C]AZD2184 had superior imaging properties in PET, as shown by larger effect sizes comparing binding potential values in cortical regions of AD patients and healthy controls. Nevertheless, probably due to a lower amount of nonspecific binding, the group separation of the distribution volume ratio values of [(11)C]AZD2995 was greater in areas with lower amyloid-β load, e.g. the hippocampus. CONCLUSION: Both AZD2995 and AZD2184 detect amyloid-β with high affinity and specificity and also display a lower degree of nonspecific binding than that reported for PIB. Overall [(11)C]AZD2184 seems to be an amyloid-β radioligand with higher uptake and better group separation when compared to [(11)C]AZD2995. However, the very low nonspecific binding of [(11)C]AZD2995 makes this radioligand potentially interesting as a tool to study minute levels of amyloid-β. This sensitivity may be important in investigating, for example, early prodromal stages of AD or in the longitudinal study of a disease modifying therapy. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00259-012-2322-6) contains supplementary material, which is available to authorized users.